Periplaneta americana Extracts Accelerate Liver Regeneration via a Complex Network of Pathways - Zou, Yingying; Zhang, Meiyan; Zeng, Di; Ruan, Yonghua; Shen, Lijuan; Mu, Zhihao; Zou, Jiangmeng; Xie, Chenjian; Yang, Zhihong; Qian, Zhongyi; Xu, Ruobing; Li, Shude; et al. (Frontiers in Pharmacology, 2020)
Successful recovery from hepatectomy is partially contingent upon the rate of residual liver regeneration. The traditional Chinese medicines known as Periplaneta americana extracts (PAEs) positively influence wound healing by promoting tissue repair. However, the effect of PAEs on liver regeneration is unknown. We used a mouse liver regeneration model after 70% partial hepatectomy (PH) and a hepatocyte culture to determine whether PAEs can promote liver regeneration as effectively as skin regeneration and establish their modes of action. L02 cells were divided into serum-starved control (NC) and three PAE (serum starvation + 0.1 mg/mL, 0.5 mg/mL, or 1 mg/mL PAEs) groups. L02 cell proliferation was assessed at 24 h, 48 h, and 72 h by CCK-8 assay. Forty male C57 mice were randomly divided into control (NC), normal saline (NS), PAEs400 (400 mg/kg/d), and PAEs800 (800 mg/kg/d) groups (n = 10 per group). The NS and both PAEs groups were administered normal saline and PAEs, respectively, by gavage for 10 d. Two hours after the tenth gavage, the NS and both PAEs groups were subjected to 70% PH and the residual liver was harvested after 48 h. The hepatic regeneration rate was evaluated and hepatocyte proliferation was estimated by immunohistochemical (IHC) staining for Ki-67. Twelve DEG libraries (three samples per group) were prepared and sequencing was performed in an Illumina HiSeq 2000 (Mus_musculus) at the Beijing Genomics Institute. The genes expressed in the liver tissues and their expression profiles were analyzed by bioinformatics. KEGG was used to annotate, enrich, and analyze the pathways. PAEs promoted hepatocyte proliferation in vitro and in vivo and accelerated mouse liver regeneration after 70% PH. The screening criteria were fold change (FC) ≥ 2 and q-value < 0.001. We identified 1,092 known DEGs in PAEs400 and PAEs800. Of these, 153 were categorized in cellular processes. The KEGG analysis revealed that the aforementioned DEGs participated in several signaling pathways closely associated with cell proliferation including PI3K-Akt, MAPK, Apelin, Wnt, FoxO, mTOR, Ras, VEGF, ErbB, Hippo, and AMPK. It was concluded that PAEs can effectively improve liver regeneration via the synergistic activation of different signaling pathways.